Effect of Profitability and Liquidity on Capital Structure and Value of Plantation Companies in Indonesia - Supeno, Ari; Ali, Hapzi; Yayuk Priyati, Rini (Dinasti Publisher, 2022)
This study aims to examine the effect of profitability and liquidity on firm value in plantation companies in Indonesia with the intervening variable capital structure on plantation companies listed on the Indonesia Stock Exchange for the period 2018-2021. The results of this study indicate that: (1) Profitability has a significant positive effect on Capital Structure; (2) Liquidity has a significant negative effect on Capital Structure; (3) Profitability has no significant positive effect on firm value; (4) Liquidity has a significant negative effect on Firm Value; (5) Capital structure has a significant negative effect on firm value; (6) The effect of statistical intervention on Capital Structure, can mediate the effect of Profitability on Firm Value; (7) The effect of statistical intervention on Capital Structure can mediate the effect of Liquidity on Firm Value.